Reviews. Issue 2 (1st June 2017) - Popescu, Maria-Irina; Posocco, Silvia; Kane, Annemarie; Tate, Shirley Anne; Bellomy, Steve; Doyle, Gavin; Witcombe, Mike; Malewitz, Raymond; Tsitsovits, Ioannis
The 'War on Terror' and American Fiction: 9/11 Frames Per Second, Terence McSweeney (2014) Edinburgh: Edinburgh University Press, 256 pp., ISBN: 9780748693092, h/bk, £70, 9781474413060, p/bk, £24.99American Cinema in the Shadow of 9/11, Terence McSweeney (ed.) (2017) Edinburgh: Edinburgh University Press, 352 pp., ISBN: 9781474413817, h/bk, £75Notes towards a Performative Theory of Assembly, Judith Butler (2015) Cambridge, MA and London: Harvard University Press, 256 pp., ISBN: 9780674967755, cloth: alk. paper, $27.95, £21.95, 25.00; ISBN: 9780674495562, epub; ISBN: 9780674495555, mobi11.22.63, J. J. Abrams, Stephen King, Bridget Carpenter, Bryan Burk and James Franco (2016) USA: HuluCritical Ethnic Studies: A Reader, Critical Ethnic Studies Editorial Collective, Nadia Elia, David M. Hernández, Jodi Kim, Shana L. Redmond, Dylan Rodríguez and Sarita Echavez See (2016) Durham, NC and London: Duke University Press, pp. 556, ISBN: 9780822361084, h/bk, $109.95; ISBN: 9780822361275, p/bk, $31.95; ISBN: 9780822374367, e-bk, $31.90Fictions of Mass Democracy in Nineteenth-Century America, Stacey Margolis (2015) 1st ed., New York: Cambridge University Press, 211 pp., ISBN-13: 9781107107809, h/bk, $103.00I Must Be Living Twice: New and Selected Poems, 1975−2014, Eileen Myles (2016) London: Tuskar Rock Press, 356 pp., ISBN: 9781781257364, h/bk, £14.99Chelsea Girls, Eileen Myles (2016) London: Serpent's Tail, 274 pp., ISBN: 9781781257807, p/bk, £8.99Home fires burningFallout 4, Bethesda Game Studios, 2015 Rockville, MD: Bethesda SoftworksTom Clancy's The Division, Ubisoft Massive, 2016 San Francisco, CA: UbisoftHomefront: The Revolution, Deep Silver Dambuster Studios, 2016 Planegg: Deep SilverOther Things, Bill Brown (2015) Chicago: University of Chicago Press, 485 pp., ISBN: 9780226076652, h/bk, $40.00Cool Characters: Irony and American Fiction, Lee Konstantinou (2016) Cambridge, MA and London: Harvard University Press, 384 pp., ISBN: 9780674967885, h/bk, £31.95